Pancasila Moral Ethics as a Philosophical Foundation for the Formulation of Copyright Law - Ananda Fairus Zakky (Pancasila and Law Review, 2025)
The philosophical foundation of copyright law in Indonesia has often been addressed normatively, yet its ethical grounding in Pancasila has not been systematically examined. This article argues that Indonesian copyright law embodies a normative synthesis between economic utilitarianism and personality-based moral rights through the ethical structure of Pancasila as the staatsfundamentalnorm of the legal system. Using a normative juridical method combined with philosophical analysis, this study examines Law No. 28 of 2014 on Copyright in light of Pancasila’s integrated moral principles. The findings demonstrate that moral rights reflect the principle of just and civilized humanity by safeguarding the dignity and intellectual identity of creators, while economic rights realize social justice through fair distribution of benefits derived from creative labor. Comparative analysis with the United States and France further reveals that Indonesia adopts a balanced model that mediates global intellectual property doctrines within its national philosophical framework. This study contributes by positioning Pancasila not merely as symbolic constitutional rhetoric, but as a substantive ethical foundation that normatively justifies the dual structure of copyright protection in Indonesia, particularly in the face of emerging digital and technological challenges.